Detection of Salmonella Typhi nucleic acid by RT-PCR and anti-HlyE, -CdtB, -PilL, and -Vi IgM by ELISA at sites in Ghana, Madagascar and Ethiopia - Panzner, Ursula; Mogeni, Ondari Daniel; Adu-Sarkodie, Yaw; Toy, Trevor; Jeon, Hyon Jin; Pak, Gi Deok; Park, Se Eun; Enuameh, Yeetey; Owusu-Dabo, Ellis; Van Tan, Trinh; Aseffa, Abraham; Teferi, Mekonnen; et al. (BMC infectious diseases, 2022)
We aimed to assess the prevalence of Salmonella Typhi through DNA and IgM-antibody detection methods as a prelude to extended surveillance activities at sites in Ghana, Madagascar, and Ethiopia.